Pregnancy in a peritoneal dialysis patient undergoing intermittent peritoneal dialysis during the third trimester of pregnancy: a case report and literature review - Z.Y. Chang; R. Cao; R.C. Xu; Y. Cheng; Q.J. Wan (IMR Press, 2020)
For patients undergoing peritoneal dialysis (PD), the rate of successfully carrying a pregnancy to term is low. Herein, we describe the pregnancy course of a patient with end-stage renal disease on peritoneal dialysis. The information presented may make better undestanding in the knowledge and management of such high-risk pregnancies in this patient population. We report the successful completion of pregnancy in a patient who underwent continuous ambulatory peritoneal dialysis (CAPD) and then switched to intermittent peritoneal dialysis (IPD) during her third trimester. She became pregnant after undergoing CAPD for almost 1 year, using four 1.5 L exchanges of 1.5% bags per day. At 30 weeks of gestation, she switched from CAPD to IPD, using six 0.5 L exchanges of 1.5% bags per day with daily ultrafiltration of 100-300 mL. Her total Kt/V was 1.72 (dialysate 1.2, residual kidney 0.5) during her first and second trimesters and her total Kt/V decreased to 1.63 (dialysate 1.15, residual kidney 0.48) during her third trimester. She was admitted to our hospital at 35 weeks of gestation for a planned lower segment caesarian section. We report the successful completion of pregnancy in a patient on IPD. We have shown that rather than pursuing an adequate weekly default value of Kt/V, the most important criterion for the optimization of dialysis treatment for pregnant patients is their medical condition.